Parental feeding practices and child-related factors are associated with overweight and obesity in children and adolescents with autism spectrum disorder - Shiang, Yen Eow; Poh, Ying Lim; Awang, Hamidin; Mohd Shariff, Zalilah (Springer New York, 2021)
Atypical eating behaviors displayed by children with autism spectrum disorder (ASD) predispose them to unhealthy weight gain. We determined the factors associated with body weight status among 261 children with ASD (3–18 years) at nine autism intervention centers. Their mothers completed a self-administered questionnaire on sociodemographic background, parenting style, parental feeding practices, parenting stress, sleep habits, eating behaviors, and autism severity. Children with older age, non-full term gestational age, high maternal perceived weight, high maternal concern about child weight, and low pressure to eat were more likely to be overweight and obese. Obesity is a major concern among children with ASD. Healthy weight management programs for parents should incorporate appropriate feeding practices and a healthy perception of body weight.